Celebrations During Covid-19 Pandemic In Udhabond Goan Panchayat Of Assam - Pinak Kanti Roy; GP Pandey (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Since the Vedic era, villages in India were considered as the unit of administration and the powers were decentralized. The Panchayats held a very important place in the public administration during Ramayana and Mahabharata periods. Similarly, during the Buddhist and Mauryan periods, Panchayats or Gram Sangh was entrusted to run the village administration of republics. From the very beginning of the First Five Year plan, planners and policy makers paid serious attention to ‘planning from below’. In 1952, the Community Development Programme was started, followed a year later by the national extension service, which envisaged an administrative set up to reach the population and to secure the fullest development of the rural community. With regards to Coronavirus, as of February 2021, the total number of confirmed cases of Corona virus in Cachar District stands at 3302, active cases are 1794, recovered cased are 1498 and deceased 10 as per the Assam government portal. The first case of Covid-19 pandemic in Assam was reported on 31st March 2020 and Silchar eing the north-east’s second gateway reported to be one of the worst affected places with coronavirus. In the fight against coronavirus, many frontline warriors of this region tested positive for Covid-19. Due to the timely steps taken by Government Authorities, which was implemented smoothly at the local Goan Panchayat level, also helped control the spread of Covid-19. Thus it became important for the researcher here to study the level of awareness people had in order to understand, how the local Udharbond Goan Panchayat at the village level worked along with the concerned government authorities in order to implement and control the spread of the virus.